У'=8x³+1/x²+4/2√4x=8x³+1/x²+1/√x
2) y'=2/cos²2x(2^x+5^x)+tg2x*(2^xln2+5^x*ln5)=2(2^x+5^x)/cos²2x+tg2x*(2^x*ln2+5^x*
*ln5)
3)f'=1+4*(-2x^-3)=1-8/x³
5) y'=(tg³x)'/2√tg³x=3tg²x/cos²x/2√tg³x=3/2√tgx/cos²x
1) Пусть первое число - х, тогда второе - (х-6)
х+(х-6)=50
2х-6=50
2х=50+6
х=56 : 2
х=28 - первое число,
28-6=22 - второе число.
2)
пусть первое х, тогда второе -(х+48).
х+ (х+48)=100
2х+48=100
2х=52
х=52:2
х=26 - первое, 26+48=74 - второе.
1.000 - (285 - х) = 820
1.000 - 285 + х = 820
715 + х = 820
х = 820 - 715
х = 105
<u>проверка:</u>
1.000 - (285 - 105) = 820
1.000 - 180 = 820
820 = 820
Неверно, 45 делится на 5 с остатком 3, а не 4
2) 5у +6,7 = 6,7
5у =0
у=0
)))))))))))))))))))))))))))